2016
DOI: 10.1103/physrevlett.116.032501
|View full text |Cite
|
Sign up to set email alerts
|

Simple Nuclear Structure inCd111129from Atomic Isomer Shifts

Abstract: Isomer shifts have been determined in [111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129] Cd by high-resolution laser spectroscopy at CERN-ISOLDE. The corresponding mean square charge-radii changes, from the 1=2 þ and the 3=2 þ ground states to the 11=2 − isomers, have been found to follow a distinct parabolic dependence as a function of the atomic mass number. Since the isomers have been previously associated with simplicity due to the linear mass dependence of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…Systematics here do not justify a tentative spin assignment, and therefore the spins must be measured directly. Yordanov et al recently performed isomeric frequency shift measurements in a collinear laser spectroscopy experiment [3,49]. While an energy difference of ∼ 250 keV would produce a frequency difference of ±1.3 MHz [50], that is approximately half the error stated in their publication [49] so laser spectroscopy alone cannot illuminate the spin assignments either.…”
Section: Discussionmentioning
confidence: 99%
“…Systematics here do not justify a tentative spin assignment, and therefore the spins must be measured directly. Yordanov et al recently performed isomeric frequency shift measurements in a collinear laser spectroscopy experiment [3,49]. While an energy difference of ∼ 250 keV would produce a frequency difference of ±1.3 MHz [50], that is approximately half the error stated in their publication [49] so laser spectroscopy alone cannot illuminate the spin assignments either.…”
Section: Discussionmentioning
confidence: 99%
“…This implies a rather large effective neutron charge of q e 2.5 n eff, = . Later it was shown that these assumptions can indeed be used to explain also the isomer shifts between the respective ground state and the isomer, which were found to follow a distinct parabolic dependence as a function of the atomic mass number [72]. Even though the nuclear shape is very close to spherical all along the isotopic chain and never exceeds a deformation parameter of 0.07, this unique regularity in the isomeric shift can be understood as a manifestation of nuclear deformation.…”
Section: New Methods and Highlights Since 2000mentioning
confidence: 99%
“…As reviewed in Ref. [78], this empirical functional has been very successful in describing nuclear ground state properties, e.g., the Coulomb displacement energies between mirror nuclei [79], nuclear binding energies [80][81][82] and quadrupole moments [83][84][85] and phase transitions in the nuclear shape [86], and low-energy excited states including nuclear chiral rotations [87] and magnetic and antimagnetic rotations [88][89][90][91][92]. PC-PK1 has also been used to study properties of SHN [93][94][95].…”
Section: As Mentioned In Section 2 a Truncation [Nmentioning
confidence: 99%